Pandangan dan Kritik Yûsuf al-Qaradâwî terhadap Pandangan Barat tentang Agama dan Ilmu Pengetahuan - Sholeh, Moh. Jufriyadi (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
This article explores the views and criticism Yûsuf al-Qaradâwî against Western views (secularism) about science. He provides awareness that religion and science have a relationship of mutual need. Religion needs science to explain the scientific facts that exist in nature. On the contrary, On the contrary, science requires religion in providing the moral basis for the application and usefulness of this science for human life and the environment. Happiness in the world is a prerequisite for achieving happiness in the hereafter, because religion is a source of knowledge and science is a means to apply everything contained in religious teachings. Both of these will reinforce each other and work together, so as to produce individuals who are devout in religion and progressive in developing science. Besides humans consists of two elements, physical and spiritual. Both of these elements has its own needs. Physical needs can be met by science, whereas the spiritual needs met by religion. If both of these needs are met, happiness in this world and in the hereafter will be achieved.